Prognostic value of plasma N-terminal pro-brain natriuretic peptide in patients with severe sepsis - Brückmann, Martina; Huhle, Günter; Lang, Siegfried; Haase, Karl Konstantin; Bertsch, Thomas; Weiß, Christel; Kaden, Jens; Putensen, Christian; Borggrefe, Martin; Hoffmann, Ursula (Circulation, 2005)
Background: Increased plasma levels of atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) have been identified as predictors of cardiac dysfunction and prognosis in congestive heart failure and ischemic heart disease. In severe sepsis patients, however, no information is available yet about the prognostic value of natriuretic peptides. Therefore, the aim of the present study was to determine the role of the N-terminal prohormone forms of ANP (NT-proANP) and BNP (NT-proBNP) in the context of outcome of septic patients. Furthermore, the effect of treatment with recombinant human activated protein C [drotrecogin alfa (activated)] on plasma levels of natriuretic peptides in severe sepsis was evaluated. - Methods and Results: Fifty-seven patients with severe sepsis were included. Levels of NT-proANP and NT-proBNP were measured on the second day of sepsis by ELISA. Septic patients with NT-proBNP levels >1400 pmol/L were 3.9 times more likely (relative risk [RR], 3.9; 95% CI, 1.6 to 9.7) to die from sepsis than patients with lower NT-proBNP values (P<0.01). NT-proANP levels, however, were not predictive of survival in our patient population. A highly significant correlation was found between troponin I levels and plasma concentrations of NT-proBNP in septic patients (r=0.68, P<0.0001). In addition, troponin I significantly accounted for the variation in NT-proBNP levels (P<0.0001), suggesting an important role for NT-proBNP in the context of cardiac injury and dysfunction in septic patients. Twenty-three septic patients who received treatment with drotrecogin alfa (activated) presented with significantly lower concentrations of NT-proANP, NT-proBNP, and troponin I compared with patients not receiving drotrecogin alfa (activated). - Conclusions: NT-proBNP may serve as useful laboratory marker to predict survival in patients presenting with severe sepsis.
Gesehen am 27.06.2022